"Children Who Speak in Their Parents' Clichés": Exploring the Broader Social Relationship Between Cultural Practices and Teacher Identity in Lithuanian Holocaust Education. Issue 2 (3rd April 2019) - Beresniova, Christine
Abstract : This article examines how broader cultural practices influence teachers teaching the Holocaust in Lithuania. This article uses the concept of the "cultural curriculum" to examine how community "stories" intersect with formal education. It finds that teachers feel they have become responsible for challenging long-standing cultural practices as well now. This is not always welcome because most are uncertain how to engage with community behaviors and preserve their place in the community at the same time.